Efectividad del Programa Educativo Desarrollando Habilidades con Estimulación Temprana para Mejorar el Nivel de Conocimientos, Actitudes y Prácticas en Madres con Niños de 2 a 5 Años de la I.E.I Nº 143, La Era, Lima 2008. - Celina Del Carmen Flores Dávila (2019)
Purpose: To determine the effectiveness of the educational program: “Developing my skills through earlychildhood education” in mothers with children from 2 to 5 years of age at the I.E.I. Nº 143, La Era-Ñaña, LimaPeru, 2008. Methodology: The present research was a pre-experimental study, the population was obtainedfrom a group of mothers who were applied the Pre and Post knowledge, attitude, and practice Test aboutearly childhood education. Right after the program was applied along with the continuous follow up throughhome visits to the group in study. The obtained data from the mothers’ Pre test and Post test were comparedutilizing the Student T test, in order to obtain a meaningful improvement of the variable being studied; thestatistical program SPSS 11.5 was used. Results: In relation to the knowledge level, it was demonstrated that8% of the mothers presented a deficient knowledge level, 23% an intermediate knowledge level, while 69%presented a good knowledge level. According to the related data to mothers’ attitude, 35% presented a negativeattitude and only 65% presented a positive attitude. In relationship to mothers’ practices, 81% presented goodpractices, while 19% displayed excellent practices. Conclusions: The educational program “Developing mySkills with Early Childhood Education” has been effective in the improvement of knowledge, attitude, and practices on early childhood education among mothers whose children were 2 to 5 year old, with a 95% of trustlevel, according to the obtained results.